A COMPREHENSIVE SURVEY OF BBTV INCIDENCE SUPPORTED BY PCR-BASED MOLECULAR VALIDATION (Journal of Plant Disease Sciences, 2023)
The Banana Bunchy Top Virus (BBTV) is a deadly disease that threatens global banana production. The purpose of this survey is to determine the prevalence of BBTV in banana plantations and to validate its presence using Polymerase Chain Reaction (PCR) analysis. A comprehensive survey was done throughout various banana-growing regions in Maharashtra state, and the virus was detected using a nucleic acid-based polymerase chain reaction (PCR) approach with four different BBTV specific primer pairs. The findings of this survey provide important information about the prevalence and distribution of BBTV in various banana growing areas. The Palghar district had the greatest disease incidence (2.5%), while Jalgon district had the lowest incidence (0.1%). The BBTV positive samples were detected by all four primerpairs, with band sizes of 350 bp for BBT1 and BBT2, 750 bp for BBT2.2, 1000 bp for DNA-C, and 1050 bp for DNA-U3.The existence of expected size PCR amplicons showed thepresence of BBTV in the obtained samples.
Keywords: Banana Bunchy Top Virus; Polymerase chain reaction; Molecular; detection,; Prevalence